WebGIS-based decision support system for soil erosion risk assessment for Guder River catchment, Ethiopia - Kedir Kemal Hajisheko; Karuturi Venkata Suryabhagavan; Karuturi Soumya (Geosystems and Geoenvironment)
Soil erosion is a crucial environmental issue affecting agricultural productivity, water quality, and ecosystem sustainability. Deforestation and human activities have led to excessive soil erosion. A webGIS-based decision support system (DSS) was developed to provide complete information on soil erosion in the Guder watershed forming a part of the Abay River Basin in Ethiopia. The parameters employed were estimated using remote sensing data. Sub-watersheds were prioritised based on soil erosion risk through a revised universal soil loss equation (RUSLE) integrated with geographic information system (GIS). The study employed high-resolution spatial data, including rainfall, soil properties, and topography, to model erosion rates across the watershed. Results indicate that the annual soil loss in the watershed varied significantly from 0 to 8021 t ha−1 yr−1, with an average loss of 97.5 t ha−1 yr−1. About 33.3% of the watershed experienced very high soil loss (>50 t ha−1 yr−1), accounting for 91.3% of the total eroded. In contrast, 25.5% of the area exhibited medium soil erosion rates (<5 t ha⁻¹ yr⁻¹). The WebGIS tool developed is powerful and user-friendly portal that enables non-technical users to access real-time soil erosion data and better understand soil conservation programs, helping them identify measures to reduce soil erosion in the watershed. Moreover, this information also supports land managers, policymakers, and farmers in adopting targeted soil erosion control measures, promoting sustainable land management in the region.